IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY (OHS) INDUCTION IN THE INTERNSHIP PROGRAM OF THE CIVIL ENGINEERING DEPARTMENT, FACULTY OF ENGINEERING, UNIVERSITAS NEGERI PADANG. - Nurpadlina, Savira Ahza; Zuwida, Nidal (Jurnal Applied Science in Civil Engineering, 2023)
The background of the research problem is that the study aims to reveal the Implementation of Occupational Health and Safety (OHS) Induction in the Internship Program at the Civil Engineering Department Workshop, Faculty of Engineering, Universitas Negeri Padang. The type of research used is descriptive research through a quantitative approach. This research was conducted at the Civil Engineering Department, Faculty of Engineering, Universitas Negeri Padang. The technique used to collect data in this study was through the questionnaire method distributed to the respondents. The respondents in this research were 8 lecturers, including 3 lecturers teaching in the wood workshop, 3 lecturers teaching in the concrete stone workshop, and 2 lecturers teaching in the plumbing and sanitation workshop, using the total sampling technique. The results of the analysis of the implementation of OHS induction in terms of 5 indicators are as follows: the OHS procedures achieved a score of 84.37% (Good), compliance with applicable regulations achieved a score of 85.41% (Good), understanding the importance of OHS achieved a score of 97.91% (Good), OHS information achieved a score of 95.83% (Good), and potential hazards achieved a score of 95.83% (Good). This means that the implementation of OHS induction in the workshop's internship program falls under the high category with an achievement rate of 91.87%.